Chemical profiling of Salix babylonica leaf extracts using HPLC-ESI-MS and their in-vivo anti-hepatotoxic effect - Eman Abdallah Morsi; Mortada Mohamed Elsayed; El-Sayed Saleh Abdel-Hameed; Ezzat El-Sayed Abdel-Lateef Osman; Tarek Abou-Shousha; Heba Abdel-Hady (South African Journal of Botany, 2026)

Seaweed Liquid Extract Improves Growth, Immunity, and Gene Expression in Nile Tilapia (Oreochromis niloticus) - Mohamed Ashour; Einar Ringø; Fawzia S. Ali; Ahmed Mamoon; Othman F. Abdelzaher; Roshmon Thomas Mathew; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Elsayed S. I. Mohammed; Hesham S. Hassanien; Mohamed A. Elokaby; Mohamed M. Mabrouk (Journal of Applied Phycology, 2026)

Iron-functionalized biochar and manure compost mitigate polyethylene microplastic toxicity in soil via enhanced performance of Solidago canadensis - Abdulmalik H. Altuwayjiri; Ishraga Galal Eldin Abdalla Awad; Malik Bader Alazzam; Saad Alrashdi; Maha Abdallah Alnuwaiser; Ahmed Mohajja Alshammari; Fathy Elsayed Abdelgawad (Journal of Environmental Chemical Engineering, 2026)

Scouting the Efficacy of Chitosan-coated Litsea Lipid Carriers Nanoplatform as an Oral Delivery System of Lornoxicam in an Inflammatory Animal Model - Walaa A. El-Dakroury; Abdelrahman R. Said; Gihan F. Asaad; Heba M. I. Abdallah; Marwa E. Shabana; Rahma A. Abdelsalam; Eman M. Elsadek; Basma H. Mohamed; Yara S. Mohamed; Sara M. Seliem; Elsayed Y. Hamada; Belal W. Attef; et al. (Journal of Pharmaceutical Innovation, 2026)
Lornoxicam-loaded chitosan-coated Litsea lipid nanocarriers (LRX-CS-LLCs) were developed as an innovative oral delivery system, combining the synergistic anti-inflammatory effects of Litsea cubeba oil with the mucoadhesive properties of chitosan. The GC/MS analysis of Litsea cubeba oil identified α -citral (47.56%), β -citral (26.86%), and D -limonene (14.00%). Various LRX-loaded LLCs were prepared and optimized. Fourier transform-infrared (FTIR) and differential scanning calorimetry (DSC) confirmed its structural integrity. The optimized (LRX-CS-LLCs) exhibited a particle size of 165.4 ± 6.3 nm, zeta potential of + 26.3 ± 3.2 mV, and entrapment effectiveness of 98.2%. In vitro release followed a controlled kinetic profile. In vivo, LRX-CS-LLCs significantly reduced carrageenan-induced paw edema (77 ± 1.86% inhibition) and PGE2, COX-2, and TNF-α levels by 4.4-, 3.6-, and 3-fold, respectively, compared to the positive control group. Histopathological examinations confirmed normal tissue architecture. Notably, LRX-CS-LLCs outperformed pure-LRX, marketed-LRX, and uncoated-LRX-LLCs, emphasizing its promise as an effective oral therapeutic approach for enhanced management of inflammatory conditions.

Omega-3 supplementation in migraine prophylaxis: An updated systematic review and meta-analysis - Haneen Sabet; Abdallah Abbas; Ibraheem M alkhawaldeh; Shrouk Ramadan; Moaz Elsayed Abouelmagd; Ebrahem Salah Abdul-Hamid; Ahmed Elbataa; Mona Mahmoud Elsakka; Anas Mansour; Mostafa Hossam El Din Moawad; Aynur Ozge (PharmaNutrition, 2025)

Enhancing ceftriaxone degradation via an optimized Fenton-like reaction using ZVI/Cu nanoparticles - Mohamed Ayoub; Abdallah Abdelfattah; Abdelaziz Elsayed Abdelaziz; Ahmed El-Morsy (Journal of Water Process Engineering, 2025)

Pyrazole derivatives ameliorate synovial inflammation in collagen-induced arthritis mice model via targeting p38 MAPK and COX-2 - Ahlam M. Abdallah; Amany H. Abdel Naiem; Salama R. Abdelraheim; Omar M. Mohafez; Hend M. Abdelghany; Sahar A. Elsayed; Wafaey Gomaa; Heba Marey (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
The type II collagen-induced arthritis (CIA) model and human rheumatoid arthritis exhibit similar characteristics. Both diseases involve the production of inflammatory cytokines and other mediators, triggering an inflammatory cascade linked to bone and cartilage damage. Recently, new pyrazole compounds with various pharmacological activities, including antimicrobial, anticancer, anti-inflammatory, and analgesic agents, have been reported. Our aim is to evaluate the therapeutic effectiveness of two newly synthesized pyrazole derivatives, M1E and M1G, in reducing inflammation and oxidative stress in a mouse model of collagen-induced arthritis. Arthritis was induced in DBA/1J mice, and the therapeutic effect of the M1E and M1G is assessed by measuring the arthritic index, quantifying the expression of inflammatory genes such as p38 MAPK, COX-2, IL1β, MMP3, and TNF-α using real-time PCR and analyzing protein expression using western blotting for phosphorylated p38 MAPK and COX-2. Oxidative stress markers and hind paws joint histopathology were also evaluated. Treatment with the two pyrazole derivatives significantly ( p < 0.001) improved the arthritic score; downregulated the expression of inflammatory genes p38 MAPK, COX-2, IL1β, MMP3, and TNF-α; and reduced the protein expression of phosphorylated p3 MAPK and COX-2. In addition, both compounds ameliorated oxidative stress by increasing the activities of SOD and reducing the formation of MDA in the paw tissue homogenates. Both M1E and M1G significantly ( p < 0.001) improved the pathological features of synovitis. The pyrazole derivatives, M1E and M1G, significantly reduced the arthritic score and the inflammatory cytokine expression, improved synovitis histopathology, and ameliorated oxidative stress in the CIA mice model.

Optimization and performance evaluation of a novel nano-zeolite amended pure oxygen-driven membrane aerated biofilm reactor (Z-PO-MABR) for enhanced carbon and nitrogen removal from high-strength wastewater - Abdallah Abdelfattah; Reham Eltawab; Hui Jia; Abdelaziz Elsayed Abdelaziz; Mohamed Ayoub; Ahmed El-Morsy; Liang Cheng (Journal of Water Process Engineering, 2024)

Upcycling of industrial pea starch by rapid spray nanoprecipitation to develop plant-derived oil encapsulated starch nanoparticles for potential agricultural applications - Rahul Islam Barbhuiya; Charles Wroblewski; Sivaranjani Palanisamy Ravikumar; Guneet Kaur; Winny Routray; Jayasankar Subramanian; Abdallah Elsayed; Ashutosh Singh (Carbohydrate Polymers, 2024)

Antagonistic Effect of Zinc Oxide Nanoparticles Dietary Supplementation Against Chronic Copper Waterborne Exposure on Growth, Behavioral, Biochemical, and Gene Expression Alterations of African Catfish, Clarias gariepinus (Burchell, 1822) - Shaimaa A. A. Ahmed; Rowida E. Ibrahim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Khaled Yehia Faroh; Samar A. El Gamal; Shereen Badr; Tarek Khamis; Abdallah Tageldein Mansour; Simon J. Davies; Mohamed ElHady (Biological Trace Element Research, 2024)

Effects of dietary commercial phytobiotic “Sanacore® GM” on Pacific white shrimp (Litopenaeus vannamei) growth, immune response, redux status, intestinal health, and disease resistance against Fusarium solani - El-Sayed Hemdan Eissa; Samia Elbahnaswy; Amira Hussein El-Baz; Ehab El-Haroun; Mohamed Ashour; Abdallah Tageldein Mansour; Saadea Saadony; Adel F. El-Saeed; Hoda Kabary; Samyah D. Jastaniah; Bothaina A. Alaidaroos; Manal E. Shafi; et al. (Aquaculture International, 2024)
The use of phytobiotic as functional feed additives is a promising inducer for growth performance and immune response in the Pacific whiteleg shrimp ( Litopenaeus vannamei ). It can be also commercially applied in combination with chemotherapeutic agents and vaccines. This study was carried out to evaluate the use of a commercial phytobiotic feed additive, Sanacore® GM, containing vegetable fatty acids and inactivated Saccharomyces cerevisiae with herbal extracts , on growth, body composition, non-specific immune response, antioxidant index, intestinal microflora count, and fungal resistance to Fusarium solani challenge in Pacific white shrimp, Litopenaeus vannamei . Shrimp juveniles (5.00 ± 0.1 g) were randomly distributed into 12 hapas (1 m 3 ) in triplicates at a stocking density of 20 shrimp per hapa and fed increasing levels of Sanacore® (0, 0.1, 0.2, and 0.3%) for 63 days. At the end of the feeding trial, the experimental shrimp were infected with F. solani , and mortality was recorded for 15 days. Results revealed that growth performance, feed utilization, and whole-body protein deposition were improved with increasing dietary sanacore levels. A significant improvement was reported in cellular (hemocyte counts, phagocytosis, phagocytic index, respiratory burst activity) and humoral (lysozyme and phenoloxidase) immune responses with higher dietary sanacore levels. Superoxide dismutase, catalase, and glutathione peroxidase were notably improved in shrimp-fed sanacore-supplemented diets. Meanwhile, malondialdehyde level was significantly decreased in all sanacore-supplemented shrimp. Furthermore, the dietary sanacore consistently increased probiotic bacterial counts and decreased enteric and Clostridium sp. counts in the intestine. Juveniles fed with Sanacore exhibited significantly lower mortality rates when challenged with F. solani . In conclusion, dietary sanacore could exhibit a profitable effect on the growth performance, antioxidant capacity, immunity, intestinal microbial, and the health condition of L. vannamei . Thus, sanacore can be used as an attractive feed supplement in the L. vannamei diet (0.2–0.3%), providing more insights into its application in aquaculture as a functional immunostimulant feed additive.

A review of nanoparticle synthesis and application in the suppression of diseases in fruits and vegetables - Rahul Islam Barbhuiya; Natalia Nevarez Tinoco; Saipriya Ramalingam; Abdallah Elsayed; Jayasankar Subramanian; Winny Routray; Ashutosh Singh (Critical Reviews in Food Science and Nutrition, 2024)

New phage-based wastewater pollution control solution with safe reuse - Mohamed I. Azzam; ElSayed E. ElSayed; Marwa M. Gado; Abdallah S. Korayem (Environmental Nanotechnology, Monitoring & Management, 2024)

In vitro and in vivo antifungal and immune stimulant activities of oregano and orange peel essential oils on Fusarium solani infection in whiteleg shrimp - Abdallah Tageldein Mansour; Elsayed A. Eldessouki; Riad H. Khalil; Amany M. Diab; Talal A. M. Abo Selema; Nehal A. Younis; Nashwa Abdel-Razek (Aquaculture International, 2023)

An Aflatoxin-M1 biochip using graphene quantum dot-gold hybrid nanoparticles - Saipriya Ramalingam; Abdallah Elsayed; Ashutosh Singh (Food Chemistry, 2023)

Physiological and immunological responses of Nile tilapia fed dietary supplementation of sweet basil ethanolic and aqueous extracts - Abdallah Tageldein Mansour; Amany M. Diab; Riad H. Khalil; Elsayed A. Eldessouki; Nasser El-Sabbagh; Salma I. Elsamannoudy; Nehal A. Younis (Frontiers in Marine Science, 2023)
The use of phytotherapy in aquaculture is rapidly increasing for more environmentally sustainable measures. The present work aimed to investigate the effects of different dietary levels of sweet basil, Ocimum basilicum , leaves ethanol (BEE) or aqueous (BAE) extracts (0, 200, 300, and 500 mg/kg) on Oreochromis niloticus growth, digestive enzyme activities, hemato-biochemical profile, antioxidant status, immune responses, and resistance against Streptococcus agalactiae . Oreochromis niloticus fingerlings (40.00 ± 1.00 g/fish, n = 210) were randomly divided into seven triplicated groups (control, BEE 200 , BEE 300 , BEE 500 , BAE 200 , BAE 300 , and BAE 500 ) and fed the experimental diets for 8 weeks. The results revealed that dietary inclusion of BEE and BAE significantly improved final weight, weight gain, survival, and digestive enzyme activities. The growth response revealed a dose-dependent in favor of fish fed BEE. The hemato-biochemical biomarkers showed a significant improvement in RBCs, WBCs, hemoglobin, and lymphocyte, and a significant decrease in aminotransferases, creatinine, and cholesterol levels with dietary basil extracts. The cellular and humoral immune responses (phagocytic activity, phagocytic index, lysozyme activity, immunoglobulin) were significantly improved with increasing BEE and BAE in a dose-dependent manner. The expression of IL-1β and TNF-α genes were increased, while TGF-β was decreased in a dose-dependent manner and BEE 500 have the highest expression. The antioxidant balance was improved with increasing basil extracts supplementation, and the BEE 500 group showed the best antioxidant status. Dietary BEE and BAE increased Nile tilapia resistance to S. agalactiae . In conclusion, the dietary supplementation of both ethanolic and aqueous extracts could improve the growth performance and physiological, and immune-antioxidant status of Nile tilapia.

Integrated process approach for degradation of p-cresol pollutant under photocatalytic reactor using activated carbon/TiO2 nanocomposite: application in wastewater treatment - Tripti Singh; Dan Bahadur Pal; Ashok Kumar Bhatiya; Pradeep Kumar Mishra; Abeer Hashem; Abdulaziz Abdullah Alqarawi; Elsayed Fathi AbdAllah; Vijai Kumar Gupta; Neha Srivastava (Environmental Science and Pollution Research, 2022)

The Ameliorative Role of 5-Aminolevulinic Acid (ALA) Under Cr Stress in Two Maize Cultivars Showing Differential Sensitivity to Cr Stress Tolerance - Ume Habiba; Shafaqat Ali; Muhammad Rizwan; Muhammad Bilal Hussain; Afzal Hussain; Pravej Alam; Abdulaziz A. Alqarawi; Abeer Hashem; Elsayed Fathi AbdAllah (Journal of Plant Growth Regulation, 2019)